PENGARUH KEPERCAYAAN, KUALITAS PELAYANAN ISLAM DAN ETIKA PEMASARAN ISLAM TERHADAP KEPUASAN NASABAH BSI KCP GENTENG BANYUWANGI - Nawal Ika Susanti; Nurul Inayah; Alfina Nuril Hidayah (Journal of Islamic Banking, 2022)
This study aims to determine and analyze the effect of trust, Islamic Service Quality and Islamic Marketing Ethics on customer satisfaction at BSI KCP Genteng Banyuwangi. This type of research is quantitative with multiple linear regression analysis. The number of samples in this study amounted to 240 respondents who are customers of BSI KCP Genteng Banyuwang. Hypothesis testing using the T test or partially shows that trust, Islamic service quality and Islamic marketing ethics have a significant effect on customer satisfaction. And through the F test it is known that trust, Islamic service quality and Islamic marketing ethics together have a positive and significant effect on customer satisfaction at BSI KCP Genteng Banyuwangi. So from the research that the researchers did, it can be concluded that trust, Islamic service quality and Islamic marketing ethics have a positive and significant effect on customer satisfaction at BSI KCP Genteng Banyuwangi either partially or simultaneously.